BIOCONCENTRATION OF CADMIUM HEAVY METAL (CD) ON GREEN MUSSLE Perna Viridis Linn, 1758 CULTIVATED IN PASARAN ISLAND WATERS, LAMPUNG, INDONESIA - Henni Wijayanti Maharani; Nurulita Nurulita; Herman Yullianto; Eko Efendi; Putu Cinthia Delis (AQUASAINS, 2019)
Pasaran Island waters is the location of green mussel cultivation (Perna viridis), where the waters has the potential to experience heavy metal pollution including Cadmium (Cd). Green mussels are filter feeders and have a slow movement, thus they have the potential to experience heavy metal bioconcentration on their bodies. The aim of this study was to determine the bioconcentration of heavy metal cadmium (Cd) in green mussels (Perna viridis) which were cultivated in the waters of Pasaran Island. Samples were collected in February 2018 in green mussel cultivating cages of Pasaran Island water with 3 and 6 cm mussel size. Sampling was taken at three stations with three replications each. The Cd content was analyzed using AAS method. The results showed that the water content of Cd at the observation location ranged from 0.022 to 0.024 mg/l. The content of Cd of mussel meat is 0.030 to 0.033 mg/kg, the value is below the threshold based on Indonesian National Standard (SNI). The BFC value of 3 cm mussel is 1.33 mg/kg, while the 6 cm mussel is 1.47 mg/kg which indicates that the green mussels on Pasaran Island are accumulatively low on Cd.